2010
DOI: 10.2175/193864710798130463
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of New Process Technology into the Wastewater Treatment Sector

Abstract: Innovative wastewater treatment technologies are developed to respond to changing regulatory requirements, increase efficiency, and enhance sustainability or to reduce capital or operating costs.Drawing from experience of five successful new process introductions from both the inventor/developer's and adopter's viewpoints coupled with the application of marketing analysis tools (an S curve), the phases of new technology market penetration can be identified along with the influence of market drivers, marketing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…The company Paques offers the technology to treat biogas from anaerobic digestion, while a licensee, the company Paquell, offers the technology in oil and gas applications. It has been noted by other researchers, notably Parker (Parker, 2011), that having a competitor is a common factor associated with successful new technology introductions. Our research and analysis uphold this finding.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The company Paques offers the technology to treat biogas from anaerobic digestion, while a licensee, the company Paquell, offers the technology in oil and gas applications. It has been noted by other researchers, notably Parker (Parker, 2011), that having a competitor is a common factor associated with successful new technology introductions. Our research and analysis uphold this finding.…”
Section: Discussionmentioning
confidence: 96%
“…The existence of competition appears to be a key factor associated with successful technology introduction, particularly in the regulated municipal utility market. It has been noted by other researchers, notably Parker (Parker, 2011), that having a competitor is a common factor associated with successful new technology introductions. Our research and analysis uphold this finding, and found that in the case of technologies, which reached higher levels of market impact, including MBBR, MBR, UV and UF, there were at least two strong competitors working to introduce the technology during the Early Adopters Stage.…”
Section: Chaptermentioning
confidence: 96%
See 3 more Smart Citations